An experimental investigation into the ‘fate’ of entrained peritectic minerals in I-type granite magmas intruded at below 2kbar. - Zarrebini, Sara Kathryn (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.